Low-rate modem for transmission of small data in medium frequency range for Arctic - P. I. Puzyrev; S. A. Zavyalov; V. V. Erokhin; V. Yu. Shein (Омский научный вестник)
In this paper, we consider the implementation of a low-rate modem for the transmission of small data, such as short text messages, distress messages, commands, notifications, coordinates, etc. The modem uses orthogonal 64-position frequency shift keying characterized by a lower probability of bit error, the possibility of non-coherent demodulation and a constant envelope. The structure of the modem is designed for implementation in software and for the implementation in languages of the description of equipment for SDR systems. The procedure of primary time synchronization, detection, frame synchronization and demodulation is considered. The use of a low-rate modem will expand the radio coverage area in the Arctic, where there are no cellular networks.